Entrepreneurship in the Digital Era - Achmad, Nur; Saputro, Edy Purwo; Handayani, Sih (Fakultas Ekonomi, Universitas Negeri Semarang, 2016)
This research aims to know about the entrepreneurship as one of the key issues related to many aspects, including its relevance to the economic, business and employment. The researches on entrepreneurship are the references to identify the success factors which supported the entrepreneurial success. The internet development in the digital age indirectly influenced the entrepreneurial ethos. It is not only influenced by the market potential and product innovation, but also by the commitments to entrepreneurship education and training model. Therefore, the studies on entrepreneurship in the industrial and developing countries are attractive. It is relevant to the internet era which provided opportunities for the development of entrepreneurial ethos, especially for the younger generation.